Sputum microRNA‐screening reveals Prostaglandin EP3 receptor as selective target in allergen‐specific immunotherapy. Issue 12 (22nd September 2021) - Jakwerth, Constanze A.; Chaker, Adam M.; Guerth, Ferdinand; Oelsner, Madlen; Pechtold, Lisa; zur Bonsen, Lynn S.; Ullmann, Julia T.; Krauss‐Etschmann, Susanne; Erb, Anna; Kau, Josephine; Plaschke, Mirjam; Winkler, Marlene; et al.
Abstract: Background: Several microRNAs (miRs) have been described as potential biomarkers in liquid biopsies and in the context of allergic asthma, while therapeutic effects on the airway expression of miRs remain elusive. In this study, we investigated epigenetic miR‐associated mechanisms in the sputum of grass pollen‐allergic patients with and without allergen‐specific immunotherapy (AIT). Methods: Induced sputum samples of healthy controls (HC), AIT‐treated and ‐untreated grass pollen‐allergic rhinitis patients with (AA) and without asthma (AR) were profiled using miR microarray and whole‐transcriptome microarray analysis of the same samples. miR targets were predicted in silico and used to identify inverse regulation. Local PGE2  levels were measured using ELISA. Results: Two hundred and fifty nine miRs were upregulated in the sputum of AA patients compared with HC, while only one was downregulated. The inverse picture was observed in induced sputum of AIT‐treated patients: while 21 miRs were downregulated, only 4 miRs were upregulated in asthmatics upon AIT. Of these 4 miRs, miR‐3935 stood out, as its predicted target PTGER3, the prostaglandin EP3 receptor, was downregulated in treated AA patients compared with untreated. The levels of its ligand PGE2 in the sputum supernatants of these samples were increased in allergic patients, especially asthmatics, and downregulated after AIT. Finally, local PGE2  levels correlated with ILC2 frequencies, secreted sputum IL‐13 levels, inflammatory cell load, sputum eosinophils and symptom burden. Conclusions: While profiling the sputum of allergic patients for novel miR expression patterns, we uncovered an association between miR‐3935 and its predicted target gene, the prostaglandin E3 receptor, which might mediate AIT effects through suppression of the PGE2 ‐ PTGER3 axis. Abstract : miR‐3935 is upregulated in sputum cells of allergic asthma patients, who received allergen‐specific immunotherapy treatement, while mRNA levels of its predicted target, the prostaglandin E2 receptor, is downregulated as its ligand PGE2 as well. PGE2 is strongly upregulated in sputum supernatants of untreated allergic patients and is reduced in patients, who received allergen‐specific immunotherapy. PGE2 levels correlate with clinical parameters, like eosinophils and symptom score.